The Samaritan Savior Age of "Tahib" is a comparative study in the Semitic holy texts: The Samaritan Savior - Al-Shammary, Nihad (lark, 2018)
The view points of the Jews and the Samaritans are, in essence one, there are only some diminutive aspects that they vary by because the fundamental doctrine is from Israel; they have disagreed with each other on incidents of the most important. The Samaritan doctrine adopted spiritual ideas for its sensitivity to the faith. Regarding their latest time and the appearance era more than the Jews who tried to close the pathway, in front of the thought of the Savior descendants of the sons of Ishmael and said that Christ peace be upon him. We also note the difference between the Samaritans and the Jews in the issue of evil spirits, and the latest time and prophecies’ for the expected promised despite the different Samaria and the Jews in the legitimacy of affiliation of Imam Al Mahdi, who guides the world to the path of truth.